Large Sample Neutron Activation Analysis of Ceramic Matrix Composites - Stamatelatos, I. E.; Vasilopoulou, T.; Tsompopoulou, E.; Blaauw, M.; Mergia, K. (HNPS Advances in Nuclear Physics, 2019)
Carbon fiber reinforced SiC ceramic matrix composites (Cf/SiC) are promising structural materials for a variety of high-temperature aerospace and energy applications. Since the matrix elements are carbon and silicon, they present low activation after neutron irradiation and therefore are materials of particular interest for fusion energy technology applications. Large Sample Neutron Activation Analysis (LSNAA) was applied to determine the elemental composition of Cf/SiC specimens joined together using a high temperature graphite based adhesive. The neutron irradiations and gamma ray measurements were performed at the BISNIS facility of the Hoger Onderwijs Reactor, TU Delft. The results of this study demonstrate the feasibility of application of LSNAA as a cost-effective method for non-destructive elemental composition analysis of whole ceramic specimens enabling the calculation of induced activity and dose rate after irradiation in different neutron spectra.